An Activatable Afterglow/MRI Bimodal Nanoprobe with Fast Response to H2S for In Vivo Imaging of Acute Hepatitis. (10th December 2021) - Zeng, Wenhui; Wu, Luyan; Ishigaki, Yusuke; Harimoto, Takashi; Hu, Yuxuan; Sun, Yidan; Wang, Yuqi; Suzuki, Takanori; Chen, Hong‐Yuan; Ye, Deju
Abstract: Accurate detection of hepatic hydrogen sulfide (H2 S) to monitor H2 S‐related enzymes' activity is critical for acute hepatitis diagnosis, but remains a challenge due to the dynamic and transient nature of H2 S. Here, we report a H2 S‐activatable near‐infrared afterglow/MRI bimodal probe F1 ‐GdNP, which shows an "always‐on" MRI signal and "off‐on" afterglow signal toward H2 S. F1 ‐GdNP shows fast response, high sensitivity and specificity toward H2 S, permitting afterglow imaging of H2 S and evaluation of cystathionine γ‐lyase (CSE)'s activity in living mice. We further employ the high spatial‐resolution MRI signal of F1 ‐GdNP to track its delivery and accumulation in liver. Importantly, F1 ‐GdNP offers a high signal‐to‐background ratio (SBR=86.2±12.0) to sensitively report on the increased hepatic H2 S level in the acute hepatitis mice via afterglow imaging, which correlated well with the upregulated CSE activity in the liver, showcasing the good potential of F1 ‐GdNP for monitoring of acute hepatitis process in vivo. Abstract : A H2 S‐activatable NIR afterglow/MRI bimodal nanoprobe F1 ‐GdNP is designed, which shows fast reaction kinetics, high sensitivity and specificity toward H2 S, offering a remarkable „off‐on" afterglow luminescence and strong „always on" MRI signal for reliable detection of hepatic H2 S and H2 S production‐relevant enzyme (CSE) with high SBR and spatial‐resolution.